Implementasi Kebijakan JKN oleh Pemberi Pelayanan Kesehatan di Kabupaten Kepulauan Anambas - Irawati Sagala; Laksono Trisnantoro; Retna Siwi Padmawati (Jurnal Kebijakan Kesehatan Indonesia, 2016)
ABSTRACTBackground: On January 1st, 2014, the implementation of NHI started in Indonesia as well as in the district of Anambas Islands accordance with the mandate of Law No. 24 in 2014. NHI policy is a top-down policy that must be implemented. On the process of implementation, the health service providers in the RSL, as the main reference in Anambas Islands, have some problems due to the characteristics’ differences of regional and limitations the District of Anambas Islands as the border areas, islands and separated-areas (DTPK). In the context of health, rural and remote areas is often associated with a state of limited public transport, poor road infrastructure, long distances to health service facilities and difficulties in recruiting and retaining health personnel. As a result there is a significant impact on the provision of adequate health care. The availability of resources is inadequate in every health facility in Anambas Islands is also an obstacle for the implementation of NHI any existing health facilities in the District of Anambas Islands must qualify credensialing set by BPJS Health.The Objective: To analyze the implementation of NHI policy by the health service providers in the District of Anambas Islands.Method: This research is using the descriptive research with qualitative methods using a single case study, design to analyze the implementation of the NHI policy established by the health service providers in Anambas Islands, which is focused on resources, bureaucratic structure and disposition.Result: Implementation of policy NHI by health care providers both in health centers and hospitals are still many have constraints such as limited power specialist, especially in hospitals, general practitioners definitive still lacking in some health facilities, the limited infrastructure in health centers and hospitals that cause will not want the patient should be referred. This adds to the burden of transportation costs to society as ocean freight rates are quite expensive though some things can be addressed as a problem of information and improvement of bureaucratic structures, but it can not prevent the public to be referred.Conclusion: The implementation of NHI policy does not match held in Anambas Islands as the border areas, islands and separated-areas area because of the benefits received by the community of NHI be limited due to so many constraints faced by health care providers. Keywords : Implementation of policy, the National Health Insurance, health service providers.ABSTRAKLatar belakang : Dengan diberlakukannya UU Nomor 24 Tahun 2014 maka pada tanggal 01 Januari 2014 Jaminan Kesehatan Nasional dimulai di Indonesia, demikian juga halnya di Kabupaten Kepulauan Anambas. Kabupaten Kepulauan Anambas merupakan kabupaten yang dikategorikan sebagai daerah DTPK. Dalam konteks kesehatan, daerah pedesaan dan terpencil sering dikaitkan dengan keadaan transportasi umum yang terbatas, infrastruktur jalan yang buruk, jarak yang jauh ke fasilitas pelayanan kesehatan dan kesulitan dalam merekrut dan mempertahankan tenaga kesehatan. Akibatnya ada dampak yang signifikan untuk penyediaan pelayanan kesehatan yang memadai. Ketersediaan sumber daya yang tidak memadai pada setiap fasilitas kesehatan di Kabupaten Kepulauan Anambas juga menjadi kendala karena dalam pelaksanaan JKN setiap fasilitas kesehatan yang ada di Kabupaten Kepulauan Anambas harus memenuhi syarat kredensialing yang telah ditetapkan oleh BPJS Kesehatan.Tujuan: Menganalisis implementasi kebijakan JKN oleh pemberi pelayanan kesehatan di Kabupaten Kepulauan Anambas.Metode: Penelitian ini merupakan jenis penelitian deskriptif dengan metode kualitatif menggunakan rancangan studi kasus tunggal terjalin untuk menganalisis implementasi kebijakan JKN oleh pemberi pelayanan kesehatan di Kabupaten Kepulauan Anambas, yang difokuskan pada sumber daya, struktur birokrasi dan disposisi.Hasil: Implementasi kebijakan JKN oleh pemberi pelayanan kesehatan baik di puskesmas maupun rumah sakit masih banyak mengalami kendala seperti terbatasnya tenaga spesialistik khususnya yang ada di rumah sakit, dokter umum yang definitif masih kurang di beberapa fasilitas kesehatan, keterbatasan prasarana di puskesmas dan rumah sakit yang menyebabkan mau tidak mau pasien harus dirujuk. Hal ini menambah beban biaya transportasi bagi masyarakat karena tarif angkutan laut yang cukup mahal walaupun beberapa hal dapat dibenahi seperti masalah informasi dan perbaikan struktur birokrasi namun hal tersebut tidak dapat mencegah masyarakat untuk dirujuk.Kesimpulan: Implementasi kebijakan JKN tidak cocok dilaksanakan di Kabupaten Kepulauan Anambas sebagai daerah DTPK karena manfaat yang diterima masyarakat dari JKN menjadi terbatas disebabkan begitu banyak kendala yang dihadapi oleh pemberi pelayanan kesehatan. Kata Kunci : Implementasi kebijakan, Jaminan Kesehatan Nasional, pemberi pelayanan kesehatan